Immunological Responses to Candida albicans I. Mouse-Thigh Lesion as a Model for Experimental Candidiasis - Pearsall, Nancy N. (1974)
A mouse-thigh lesion model for experimental candidiasis is described. A standard inoculum of 5 × 10(8) yeast cells of Candida albicans, injected into the thigh muscle of C57BL/Ks mice, produced an easily measured thigh lesion that was self-limiting by 4 to 6 weeks, permitting a study of immunological responses to the infection. Examination of the histopathology of the lesion reveals that the cellular infiltrate is predominately granulocytic, and gives little evidence for an active, specific, cell-mediated immune response.